(3cJGH aj GdWHs - (3eLghds; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3GdEScfOQjI s)
(3ChdgG (B:s
(3CeG HYO , aEf GdQZHI ai GdYde ef GdQTGO GdPi jgOi Gddg dg ef jTGA ef YHGOg s
(3BNQgG (B:s
(3hEPG JecfJ gPg GdMei YSQ YdGLgG hJYPQ RhGdgG JeJ GdebGdI s
(3jTJed Ydi YTQI ebGdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs